MODEL INTERAKSI STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN HUTANG DAN DIVIDEN DALAM PERSPEKTIF TEORI KEAGENAN PADA PERUSAHAAN MANUFAKTUR GO PUBLIK DI INDONESIA - Suyatmini, Suyatmini; Triyono, Triyono; Wahyuddin, Muhammad (Jurnal Pendidikan Ilmu Sosial, 2013)
The aims of the research are: (1) to find out the structure of stock ownership at the public companies in Indonesia, (2) to analyze effects of stock ownership structure by insider ownership and institutional investor on debt policy and dividend policy at the public companies in Indonesia, (3) to obtain empirical evidences that control mechanism through stock ownership by the insider ownership and the institutional investor will decrease the problems of agency, which then minimizes the cost of agency,(4)to fain out simultaneous relation between the insider ownership, the institutional investor, the debt policy, and the dividend policy. The samples of the research which included 70 manufacturing companies registered at the Jakarta Stock Exchange. The samples were taken by using a purposive sampling technique. The hypotheses were then tested by means of a simultaneous analysis of Two Stage Least Square. The results of the research show that (1) the insider ownership has a significant effect on the debt policy and, there is a substitution or negative causal relation between the insider ownership and debt policy; (2) the institutional investor has a significant effect on the debt policy, and there is a substitution or negative causal relation between the institutional investor and the debt policy. (3)the institutional investor has a negative effect onthe insider ownership, (4)the dividend policy does not have a significant effect on the institutional investor, (5) there is a substitution relation between the debt policy and the dividend policy.